The role of natural killer cells in the immune response to hepatitis C virus - Ní Chorcora, Cáit Eilís (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2016)
Hepatitis C virus (HCV) infection remains a major clinical problem, particularly in the developing world where high cost makes treatment inaccessible to many. Those coinfected with HIV also face poorer prognosis and increased risk of chronic HCV infection. There is currently no vaccine publicly available for prevention of HCV infection. Several studies, including research from the Gardiner group, have suggested that NK cells play an important role in the immune response to HCV. Several NK cell genes have been identified as predictors of long-term prognosis in HCV infection. These include several genes encoding for NK cell Killer Immunoglobulin-like Receptors (KIR) as well as genes encoding their ligand. Human leukocyte antigen (HLA).
Keywords: Biochemistry & Immunology, Ph.D.; PhD Trinity College Dublin, 2016